1834 Mo. Laws 536-37 - (:unkn) unknown (My University, 1834)
An Act to Organize Govern and Discipline the Militia, ch. 423,§art.§11, pt. 5.: Every non-commissioned officer and private, appearing without being armed and equipped as the law directs, at any parade or rendezvous, shall be sentenced to pay the following fines, namely: For want of a sufficient sword and belt, if belonging to the artillery or light artillery, and for want of a sufficient musket with a steel rod, or rifle, if belonging to a company of light infantry, grenadiers, riflemen or infantry, one dollar
Keywords: ARMED FORCES